Filling the Gap: Integrating HIV into the Counselor Education Curriculum - J. Richelle Joe; Roseina D Britton; Tiffany Hairston (Teaching and Supervision in Counseling, 2025)
People living with HIV (PLWH) are vulnerable to mental health conditions including depression, anxiety, and substance use disorders, which in turn, often affect their health outcomes. Multiple, overlapping structural and social determinants of health exacerbate the physical and mental health concerns of PLWH, presenting a need for services that are responsive to the unique implications of the illness. Professional counselors have the potential to provide such services but must be adequately prepared to do so. In response to the lack of HIV-related professional development for counselors and the minimal preparation of counselors-in-training to serve clients with HIV, this article uses the 2024 CACREP standards of accreditation to provide a framework for infusing HIV-related coursework into counselor training. By aligning HIV education with CACREP's eight core areas, we address a critical gap in counselor preparation, emphasizing ethical practice, cultural competence, and practical applications at the intersection of HIV and mental health.
Keywords: HIV; graduate counseling programs; standards of accreditation; CACREP